2020
DOI: 10.21608/ejhc.2020.177145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Digital Cardiac Rehabilitation Program on Self Efficacy of Patients with Coronary Artery Diseases

Abstract: Background: Coronary artery disease is the umbrella term for a spectrum of diseases caused by myocardial ischemia decreasing blood supply to the heart muscle. Self-efficacy is a vital modifiable personal resource affecting rehabilitation adherence, and disease outcomes such as health-related quality of life among people with cardiovascular disease. Aim: To evaluate the effect of digital cardiac rehabilitation program on self efficacy of patients with coronary artery diseases. Subjects and method: Design: A qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…Therefore, and since there is only little literature on this topic so far, prospective studies might be indicated to get a deeper insight into the relationship between intrinsic motivation and digital tools during CR. Unlike a previous study by Salah Eldin Saad et al which showed significant differences in selfefficacy [29], our study indicates that self-efficacy neither differed between patients with and without digital tools, nor was there a significant correlation with the achieved change in exercise capacity. In part, this result can be explained by the retrospective nature of the EPICURE study.…”
Section: Comparison With Prior Workcontrasting
confidence: 99%
“…Therefore, and since there is only little literature on this topic so far, prospective studies might be indicated to get a deeper insight into the relationship between intrinsic motivation and digital tools during CR. Unlike a previous study by Salah Eldin Saad et al which showed significant differences in selfefficacy [29], our study indicates that self-efficacy neither differed between patients with and without digital tools, nor was there a significant correlation with the achieved change in exercise capacity. In part, this result can be explained by the retrospective nature of the EPICURE study.…”
Section: Comparison With Prior Workcontrasting
confidence: 99%
“… 58 Additionally, the digital cardiac rehabilitation program also positively influences patient knowledge and cardiac SE. 56 Then, the Nurse-Led Phone Follow-up Education Program is considered to improve SE and facilitate achieving goals related to risk factors in patients with cardiovascular disease for at least one year. 57 Therefore, some of these strategies are expected to increase SE in CHD patients, thus increasing SE will align with increasing patient QoL.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Interventions with a health digitalization approach are also reported to have good efficacy in the long-term continuity of care for CHD patients. 56 Several previous studies have shown that the effective use of technology can help improve SE in CHD patients. [57][58][59] Studies in Iran show that multimedia-based education is effective in increasing SE and selfesteem in patients with acute coronary syndromes.…”
mentioning
confidence: 99%
“… 59 , 60 In addition, the digital cardiac rehabilitation program also positively affects knowledge and SE in CHD patients. 61 Therefore, some of these strategies are expected to increase SE in CHD patients so that the increase in SE will align with the increase in QoL in patients with CHD.…”
Section: Discussionmentioning
confidence: 99%